AS CONTINGÊNCIAS HISTÓRICAS E O ENSAIO PRECOCE DO QUE SE CONSOLIDARIA COMO O PROCESSO DE INTERNACIONALIZAÇÃO DA UFSC - Sonia Pereira Laus (Universidade Federal de Santa Catarina, 2011)
This article presents an overview of the internationalization process of the Federal University of Santa Catarina, focusing on activities developed during the 1960/1970 decade at University Administration postgraduate course in collaboration primarily with Latin American institutions and having a triggering factor agreement MEC/USAID. The study lists the main international academic rankings and its elements of evaluation, with emphasis on World Universities ranking on the Web-Webometrics and Ibero-American Science and International Production, highlighting the position of same UFSC, concluding with a critique of the indicators proposed by the homogenization now adopted by international organizations and by CAPES.